Psychological impact of the modern children’s entertainment industry: a comprehensive analysis of educational, social and emotional aspects - D. S. Gibson (Путеводитель предпринимателя)
This study examines the psychological impact of the children’s entertainment industry, focusing on the multisensory environment of entertainment centers and their influence on cognitive and emotional development. Through a comprehensive analysis of existing literature and case studies, we investigate the long–term effects of regular visits to these centers on children’s psychological development. The research reveals that well–designed entertainment centers can positively influence cognitive functions, emotional intelligence, and social skills. However, potential risks such as overstimulation and dependence on external stimuli are also identified. The study emphasizes the need for a balanced approach in designing these spaces, integrating educational elements with entertainment. Our findings contribute to the understanding of how the children’s entertainment industry can be optimized to support healthy psychological development, highlighting the importance of interdisciplinary collaboration between psychology, pedagogy, and business in this field.